2021
DOI: 10.1093/ajcn/nqab026
|View full text |Cite|
|
Sign up to set email alerts
|

Dairy consumption and mortality after myocardial infarction: a prospective analysis in the Alpha Omega Cohort

Abstract: Background Population-based studies generally show neutral associations between dairy consumption and ischemic heart disease (IHD) mortality, whereas weak inverse associations were found for cardiovascular disease (CVD) and stroke mortality. Whether dairy consumption affects long-term survival after myocardial infarction (MI) is unknown. Objectives We studied types of dairy and long-term mortality risk in drug-treated post-MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Dietary guidelines for adult populations generally include two-three daily servings of dairy [10,42]. In our cohort of post-MI patients, we previously found an inverse association between (plain) yogurt consumption and long-term risk of CVD mortality [21]. The present analysis showed neutral findings for T2D, so the cardioprotective association that we observed for yogurt may be related to other (yet unknown) pathways.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Dietary guidelines for adult populations generally include two-three daily servings of dairy [10,42]. In our cohort of post-MI patients, we previously found an inverse association between (plain) yogurt consumption and long-term risk of CVD mortality [21]. The present analysis showed neutral findings for T2D, so the cardioprotective association that we observed for yogurt may be related to other (yet unknown) pathways.…”
Section: Discussionsupporting
confidence: 49%
“…In Dutch post-MI patients from the Alpha Omega Cohort, a healthy dietary pattern was associated with a~30% lower mortality risk [20], on top of cardiovascular drug treatment. In a more recent analysis in this cohort, yogurt consumption was inversely associated with cardiovascular mortality (HR: 0.96; 95% CI: 0.93 to 0.99, per 25 g/d) [21]. Whether dairy consumption affects the risk of T2D after MI is at present unknown.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…In contrast, a recent report suggests a protective link between yogurt consumption and CVD. Cruijsen et al have recently reported that during a 12year follow-up of the Alpha Omega Cohort from the Netherlands, that included 48,473 person-years and 2035 deaths, yogurt consumption was inversely associated with CVD mortality (HR 0.96 per 25 g/d) and all-cause mortality (HR 0.98 per 25 g/d) in patients with a history of myocardial infarction [12].…”
Section: Dairy Consumption and Cardiovascular Diseasementioning
confidence: 99%
“…Studies conducted in recent years stated that there is a negative relationship between the consumption of fermented milk products and the risk of CVD [ 59 , 62 ]. In post-MI patients, each 25 g/d increase in yogurt consumption, regardless of fat content, was found to reduce the CVD-related mortality risk by 4% and the overall mortality risk by 2%, while no such association was observed in other dairy products such as milk and cheese [ 89 ].…”
Section: Involvement Of Dairy Labs In the Modulation Of Non-communicable Diseases (Ncds)mentioning
confidence: 99%